Electricity generation and recovery of iron hydroxides using a single chamber fuel cell with iron anode and air-cathode for electrocoagulation. (15th December 2015) - Kim, Jung Hwan; Park, I Seul; Park, Joo Yang
Graphical abstract: Highlights: This iron–air fuel cell can replace traditional electrocoagulation water treatment. Main reactions were investigated to produce electricity and iron hydroxides. An initial pH 5 was the optimal condition for producing maximum power density. The power density output can reach up to 4343 mW/m 2 . Iron hydroxides with magnetite and maghemite were recovered at initial pH 7.5–8.5. Abstract: The use of a single chamber fuel cell with an iron anode and air cathode is a new and innovative concept in electrocoagulation. In this study, we investigated the predominant reactions that contribute to the production of electricity and iron hydroxides in solution. Solutions composed of 0.06 M NaHCO3 and 0.05 M NaCl at an initial pH of 5 were determined to be optimal for producing the maximum power density of 1997 mW/m 2 after 24 h. Increases in the bicarbonate concentration and ionic strength of the solution induced a corresponding decrease in the anode potential and increase in the cathode potential, which resulted in an increase in the cell potential and power density. Further, increasing the NaHCO3 concentration to 0.1 M and the ionic strength of the solution to 0.56 M induced an increase in the maximum power densities to 2436 and 4343 mW/m 2, respectively. Initial pH values of 7.5 and 8.5 in solutions containing 0.06 M NaHCO3 and 0.05 M NaCl were employed to synthesize magnetic iron hydroxides including magnetite and maghemite. These results suggest that this fuel cell technology can be used not only for electrocoagulation with the removal of contaminants, but also for producing useful products such as electricity and magnetic iron hydroxides. Advances in waste water air-metal fuel cells will enable more efficient power generation and systems suitable for scale-up.